KERION TYPE OF TINEA CAPITIS TREATED WITH DOUBLE PULSE DOSE TERBINAFINE - Chandra, Franky; NH, Risa Miliawati; R, Lies Marlysa (Indonesian Journal of Tropical and Infectious Disease, 2016)
Background: Tinea capitis is a common dermatophyte infection affecting hair and skin which always requires systemic treatment to get a clinical and mycologic cure, preventing relapse, and infection spread. Griseofulvin has been the antifungal therapy of choice for tinea capitis, but it often requires higher doses and a longer duration than recommended. Thus, effective alternative antifungal with good oral tolerability and shorter course of treatment are therefore required. The objective of this report is to evaluate the effectiveness of double pulse dose terbinafine for tinea capitis alternative therapy. Method: A case of kerion type of tinea capitis in a two-year-old girl was reported. Diagnosis was established based on clinical manifestations of alopecia, presented as erythematous macule with pustules, hemorrhagic crusts, and scales on the scalp, accompanied with occipital lymphadenopathy. Fungal culture showed growth of Microsporum canis (M. canis) colonies. Patient was treated with doubled pulse dose terbinafine 125 mg/day and 2% ketoconazole shampoo for two months. Result: Clinical improvements were found on 35th day of follow up, while mycologic cure was achieved on 60th day of follow up. Tolerability was excellent and no side effects observed. Conclusion: Double pulse dose terbinafine is effective for kerion type of tinea capitis.